Konsep Hukum Penyelesaian Sengketa Harta Bersama di Indonesia (Analisis Perkara No.195/Pdt.2013/PA.Mtr, Putusan No.04/Pdt.G/2014/PTA.Mtr, dan Putusan No.629 K/Ag/2014) - Kamarusdiana Kamarusdiana; Daniel AlFaruqi (JURNAL INDO-ISLAMIKA, 2016)
This paper argues that a judge has a huge impact on solving a dispute of a joint wealth for a divorced couple in Indonesia as the judge has his/her own way to establish justice in allocating the wealth not only for the divorced husband, but more importantly for the divorced wife equally. This article bases this argument on normative resources of Islamic law about the joint wealth of the divorced couples and on western views about the same issue, and compare them to the case of this issue brought in the Mataram Religious Court, in the Mataram High Religious Court, and in the national Supreme Court. Keywords: joint wealth dispute, solution, normative views of the joint wealth, and a case study of the dispute in the Mataram Religious Court.